Youth and the state in Hungary : capitalism, communism, and class - Kürti, László, 1953- (Anthropology, culture, and society., 2002)
This work takes as its focus the nature of Hungary's youth movements since the 1930s. In a detailed ethnographic study, the text covers the lives of youth workers in the Csepel district of Budapest in the context of the political and economic transformations witnessed during the 20th century.